ANALISIS CITIZEN CHARTER PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GORONTALO - Dikson Junus; Muten - Nuna; Nirmala Afriyanti Sahi; Nur Istiyan Harun; Sri Logita Purnamasari (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
ABSTRACT. Implementation of public services for the realization of good governance (good governance), one of which is through citizen charters. This citizen charter is a public service-oriented policy that places citizens or citizens at the center of public service goals. It means that the needs and interests of users of public services are the main goals. Citizen charters encourage organizers to fulfill rights and obligations as well as balance them and make citizen satisfaction a performance achievement. This research aims to identify and analyze the concept of developing good governance through citizen charters at Population and Civil Registration Department of Gorontalo Regency. The method used is descriptive research using a qualitative research approach, namely using interview data in the form of sentence descriptions. The data collection technique used in this research is by observing, documenting, and interviewing, where the researcher will conduct a question and answer directly with the selected informants. After the data is collected, it will be analyzed using interactive model data analysis techniques from Miles, Huberman, and Saldana (2014; 14) which includes data collection, data condensation, data presentation, and conclusions. The results showed that the development of good governance through citizen charters at the Population and Civil Registration Department of Gorontalo Regency was based on indicators in the citizen charters as intended (Karjuni Dt. Maani, 2010), namely vision and mission, service standards, service flows, complaint units/sections community, and surveys of service users that have not been carried out optimally. This can be seen from several indicators in the implementation of citizen charters such as the vision and mission that have not been fully implemented properly, service standards, service flow that still seems convoluted, community complaint units that are still not widely known by service users, as well as surveys of service users in determining the index of community satisfaction with services at Population and Civil Registration Department of Gorontalo Regency from 2019-2020 did not experience a significant increase, but only decreased by around 2.89%.